2019
DOI: 10.1111/jan.14098
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to diabetes care: Knowledge of biochemical processes has a high impact on glycaemic control among adolescents with type 1 diabetes

Abstract: Aim To evaluate the impact of patients’ understanding of biochemical processes involved in glucose regulation (causal‐biochemical knowledge) and of diabetes self‐management knowledge on adherence to treatment recommendations among adolescents with type 1 diabetes mellitus. Design A cross‐sectional study. Methods Adolescents with type 1 diabetes mellitus, aged 12–18 years and able to read and write in Hebrew or in Arabic were eligible. Participants were recruited between August 2016 – January 2018 during routin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The current study revealed that there was a significant improvement in the mother's adherence on posttest than pretest. This result was consistent with Dagan et al, 2019 who conducted a study about "Adherence to Diabetes Care: Knowledge of Biochemical Processes have a High Impact on Glycemic Control Among Adolescents with Type 1 Diabetes", they stated that causal-biochemical knowledge is a valuable component for the adherence to diabetes care and glycemic control. This result was consistent with Mahfouz et al, 2018 they conducted a study about "Effects of Mothers' Knowledge and Coping Strategies on the Glycemic Control of Their Diabetic Children in Egypt" they stated that the mothers with more knowledge about diabetes and with better education were able to maintain a better glycemic control of their children.…”
Section: Diabetessupporting
confidence: 88%
“…The current study revealed that there was a significant improvement in the mother's adherence on posttest than pretest. This result was consistent with Dagan et al, 2019 who conducted a study about "Adherence to Diabetes Care: Knowledge of Biochemical Processes have a High Impact on Glycemic Control Among Adolescents with Type 1 Diabetes", they stated that causal-biochemical knowledge is a valuable component for the adherence to diabetes care and glycemic control. This result was consistent with Mahfouz et al, 2018 they conducted a study about "Effects of Mothers' Knowledge and Coping Strategies on the Glycemic Control of Their Diabetic Children in Egypt" they stated that the mothers with more knowledge about diabetes and with better education were able to maintain a better glycemic control of their children.…”
Section: Diabetessupporting
confidence: 88%
“…This questionnaire was developed by the authors to evaluate mechanistic reasoning of biochemical processes in diabetes . The instrument consists of three open‐ended questions to evaluate two domains: (a) knowledge about biochemical processes of glucose regulation, and (b) components of mechanistic reasoning that address biochemical processes of glucose regulation in diabetes from a complex systems approach (including micro‐ and macro‐levels, and micro‐macro causal links).…”
Section: Methodsmentioning
confidence: 99%
“…Surface processing is the learning of factual or procedural information that does not require one to think about the meaning behind the concept. Conversely, deep processing is associated with learning that allows one to meaningfully interpret information, obtaining an understanding of causal links regarding how and why certain things work [ 30 , 31 , 32 , 33 , 34 ]. Having more cohesive causal information promotes better retrieval of previously learned facts and allows people to make predictions, understand implications, draw inferences, and offer explanations, all of which are necessary for problem-solving protective behaviors during an infectious disease outbreak [ 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%